Effectiveness of Comprehensive Diabetes Care (CDC) in Diabetic Patients: an Observational Study - Sane, Rohit; Mandole, Rahul; Amin, Gurudatta Anand; Ghadigaokar, Pravin; Paranjape, Sneha (International Journal of Innovative Research in Medical Science, 2020)
Background: Globally, Diabetes mellitus (DM) is one of the commonest non-communicable disease to contribute to morbidity and mortality. Its prevalence is increasing dramatically in India and worldwide. Comprehensive Diabetes Care (CDC) is a form of Ayurvedic therapy which combines panchkarma and diet management. Aims and objectives: The present study was done to analyze the effectiveness of CDC on glycosylated haemoglobin (HbA1c), body mass index (BMI), body weight, abdominal girth and dependency on conventional therapy in DM Patients. Materials and methods: This observational study was conducted in July 2018, wherein the data of type 2 DM patients (HbA1c >6.5%) who attended out-patient departments (OPDs) at Madhavbaug clinics across India were identified. Data of patients who were administered CDC (60-75 minutes) with minimum 6 sittings over 12 weeks were considered. All the glycemic parameters were compared at baseline and week 12. Results: Out of 1718 type 2 diabetic patients, 893 were males (52%), while 825 were females (48%), thus male: female ratio was 1.08:1. CDC showed significant improvement in HbA1c 1.64% (from 8.64 ± 0.93 to 7.00 ± 1.73; p<0.001), BMI by 1.68 (from 27.35 ± 1.34 to 25.67 ± 1.06, p= 0.04), weight by 4.37 kg (from 70.71 ± 11.28 to 66.37 ± 12.27, p=0.05). Abdominal girth (from 95.48 ± 9.74 to 90.17 ± 11.93; p=0.01), also showed significant reduction. At the end of week 12 controlled DM status was seen in 1025 patients. Dependency on concomitant medicines was significantly reduced. Conclusion: Form the findings of present study, CDC has been found to be effective owing to its dual action i.e. reduction in HbA1c and dependency on conventional antidiabetic drugs.